‘Embroidering Dreams into Veils’: Negotiating Identity and Religious Tolerance via Art in The Girl in the Tangerine Scarf - Shahzad , Aleena (Journal of Research in Humanities, 2023)
The literary impetus of Arab Muslim female writers transcends the geographical borders where certain stereotypical ideas are being impinged on them in various historical periods. Fatima Tobing Rony points out that colonial ethnography has divided the world into ‘people without history, without writing, without civilization, without technology, without archives. Amidst myriad constraints that Arab Muslim female writers endured during t h e critical period’s no female cinema, confined domestic roles, a woman who speaks in a low voice behind the curtains, publishing their work in newspapers and magazines with their pseudonyms or initial letter only, artistic immobility has given a sense of belittlement when it comes to artistic creativity. The present essay takes a departure from past notions and encapsulates the rich journey of Syrian American female Muslim who negotiated her identity in a rich multiculturalist society by practicing and questioning the essence of Islam and finally pursuing a photography career. My paper also analyzes that the camera consciousness has a pivotal role in the enlargement of human perception for religious tolerance which can’t be achieved by the human eye. Moreover, the travel writing experience of Mohja Kahf, a Syrian American writer, also gives a palpable embodied experience to the literary texture of this novel that amplifies my paper’s critical aesthetics. By trespassing Gender Borderlands, the changing colors of the scarf of the Syrian Muslim female character in the novel synchronize with her psychic mobility. She explored the true essence of Islam by dismantling the beliefs her conservative family impinged in every inch of her life. Identity negotiation in the rich bifurcation of Islam and art is the cornerstone debate of my paper that reconfigure the aesthetic style and literary representation of Arab Muslim female writing in academia and the world at large